Evaluation of Behaviour of Child and Acceptance of Multicoloured and Conventional Composite Materials: A Split-mouth Randomised Clinical Study - Nilam Vitthalrao Honaje; Nupur Suresh Ninawe; Arti Rameshwar Dolas; Surendrakumar Kaluram Bahetwar; CK Anija; Suyash Sanjay Joshi (Journal of Clinical and Diagnostic Research, 2024)
Introduction: The most crucial abilities for a Paediatric Dentist involve evaluating and managing children based on their behaviour. Children are often motivated to choose coloured restorative materials. They tend to hold their new fillings in high regard and are usually fascinated by the new materials in their oral cavity. Consequently, they are more likely to maintain the restoration, which greatly enhances their overall oral hygiene and fosters a favourable attitude towards therapy. Aim: To evaluate the behaviour of children and their acceptance of multicoloured and conventional composite materials: A randomised controlled trial. Materials and Methods: A split-mouth, single-blinded, randomised clinical study was conducted on 25 patients with Class I occlusal caries at the Department of Paediatric and Preventive Dentistry, Government Dental College and Hospital (GDCH), Nagpur, Maharashtra, India, from July 2023 to January 2024. Healthy children aged between 5 and 10 years, who were visiting the dentist for the first time, were selected from the Department of Paediatric and Preventive Dentistry. The chidren were divided in two groups-group 1, 13 (52%) children with blue coloured composite restorations and group 2, 12 (48%) chidren who received conventional composite restorations. Behaviour was assessed using the modified behaviour rating scale before and after treatment. Data analysis was performed using Statistical Package for Social Sciences (SPSS) software version 16.0 with the Wilcoxon’s Signed-rank Test. Results: Among total of 25 children, 14 (56%) were males and 11 (44%) were females with a mean age of 8.47±1.59 years. There was a significant improvement in the behaviour of children after treatment with blue coloured compomer (p-value<0.001), whereas the change in behaviour in the conventional composite group was non significant (p-value=0.157). Conclusion: Coloured restorative materials, such as blue compomer, show promising results in paediatric dentistry by promoting positive behaviour and satisfaction among children, potentially enhancing oral hygiene practices.